Ranjit Singh : The Lion of the Punjab - Osborne, W. G. (New Delhi Rupa & Co., 2002)
Ranjit Singh, 1780-1839, Maharaja of the Punjab.
Include Index
Keywords: Ranjit Singh, Maharaja of the Punjab, 1780-1839